Analysis of Job Rotation and Position Promotion on the Performance of National Social Security Agency for Employment Employees - Intan Sekar Sari; Sari Marliani; July Yuliawati (PT. Berkah Digital Teknologi, 2025)
Purpose of the study — This research aims to determine and analyze the effects of job rotation and job promotions on employee performance at BPJS Employment Karawang. Research method— The study employs qualitative descriptive methods, utilizing interviews and observations. A total of 3 respondents were involved in the research. Result— The findings indicate that: 1) job rotation is conducted according to management needs, typically lasting between 2 to 5 years; 2) promotions are based on assessments, and those who pass are elevated to higher positions; 3) employee performance improves after job rotation and promotions, measured by Key Performance Indicators (KPIs), which are considered effective in providing enriching experiences and minimizing personal conflict. Conclusion— Job rotation and promotions contribute positively to enhancing employee performance at BPJS Employment Karawang.